Harmonic Analysis of Fuzzy Logic Controller Based Active Filter Unit Using Resonant Current Control in Distributed Power System - B, Pattabhiram.; Veerraju. M, Sai (International Journal of Engineering and Technology, 2018)
Wide-ranging utilize of nonlinear loads creates harmonic resonance issues in radial distribution system. HarmonicÂ Â Â Â amplification occurring at different locations in the radial line are due to the behavior of active filter as a harmonic admittance rather conductance. This paper presents fuzzy logic controlled active filter by using resonant current control to damp a harmonic resonance. For controlling active filter as an approximately pure harmonic conductance, collections of different parallel band-pass filters are tuned for resonant current controller at harmonic frequencies. A MATLAB/SIMULINK results illustrate that the fuzzy logic controller based active filter improves higher damping performance correlated with alternative techniques.Â Â